KEBIJAKAN TARIF IMPOR PAHA AYAM DALAM MELINDUNGI INDUSTRI PERUNGGASAN NASIONAL - MASDJIDIN SIREGAR; I WAYAN RUSASTRA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2003)
The objectives of this paper are to analyze the competitiveness and comparativeadvantage of broiler production and to recommend alternative policies on import tariff andnon-import tariff barriers for chicken leg-quarter (CLQ), aimed at protecting the nationalbroiler industry. The results of the analysis indicate that Indonesia has the comparativeadvantage of whole chicken, but not in the form of parting chicken, particularly CLQ. Underan assumption that the profit of broiler industry is at least 20 percent of the total broilerproduction costs, the import tariff rate for CLQ should be 100 percent of CIF value of US630/ton. Should the profit be 25 percent and 30 percent of the total broiler production costs,the fair tariff rates would be 110 percent and 120 percent. Such an import tariff policy forCLQ should be complemented by several strategic non-tariff policies, i.e.: (i) ASUH policy(save, healthy, whole and halal) which is considered comprehensive and effective; (ii) overallreview on the implementation of halal conditions in USA; (iii) import quantity barrier forCLQ as raw material for processed meat industry; (iv) smuggling abolition and lawenforcement as the consequences of a high import tariff implementation; and (v) for theurgency and the economic viability of the national broiler industry, it is essential to carry outpolitical lobby to limit or even to stop CLQ export from USA to Indonesia.